Predictions of New Neutron-Rich Isotopes at N = 126 in the Multinucleon Transfer Reaction 136Xe + 194Ir - Jiang, Xiang; Wang, Nan (Frontiers in Physics, 2020)
Aiming to produce new neutron-rich nuclei at N = 126, the multi-nucleon transfer reactions 136Xe+194Ir, 208Pb are investigated by using the GRAZING model and the three-dimensional time-dependent Hartree-Fock (TDHF) approach. Deexcitation processes of the primary fragments are taken into account in both models. Comparison with the experimental data of 136Xe+208Pb at Ec.m. = 450 MeV indicates that the isotopic production cross sections around the entrance channel can be well reproduced by both models. The results of GRAZING indicate that 136Xe+194Ir is a promising candidate for producing new neutron-rich isotones with N = 126. The limitation of using TDHF to investigate multi-nucleon transfer reactions is also discussed.